2012
DOI: 10.1002/ijc.27746
|View full text |Cite
|
Sign up to set email alerts
|

Frizzled homolog proteins, microRNAs and Wnt signaling in cancer

Abstract: Wnt signaling pathways play important roles in tumorigenesis and are initiated by binding of Wnt to various receptors including frizzleds (FZDs). FZDs are one of several families of receptors comprised of FZD/LRP/ROR2/RYK in the Wnt signaling pathway. Expression of some FZD receptors are up-regulated, thereby activating the Wnt signaling pathway and is correlated with cancer malignancy and patient outcomes (recurrence and survival) in many cancers. The FZD family contains ten genes in humans and their function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 153 publications
(255 reference statements)
4
74
0
Order By: Relevance
“…FZDs have been identified as seven transmembrane receptors of the WNT ligands, which transduce the signals of canonical and non-canonical WNT signalling [105]. In VCaP prostate cancer cells with TMPRSS2-ERG gene fusion and invasive U87R4 glioma cell line, FZD4 induced WNT/b-catenin signalling activation, loss of E-cadherin and overexpression of Snail1 [106,107].…”
Section: Mirna-mediated Post-transcriptional Regulation Of the Wnt/b-mentioning
confidence: 99%
“…FZDs have been identified as seven transmembrane receptors of the WNT ligands, which transduce the signals of canonical and non-canonical WNT signalling [105]. In VCaP prostate cancer cells with TMPRSS2-ERG gene fusion and invasive U87R4 glioma cell line, FZD4 induced WNT/b-catenin signalling activation, loss of E-cadherin and overexpression of Snail1 [106,107].…”
Section: Mirna-mediated Post-transcriptional Regulation Of the Wnt/b-mentioning
confidence: 99%
“…Moreover, also in Chinese patients, the survival analyses results showed that patients with high expression levels of hsa-miR-335 had reduced overall survival rate and high recurrence risk of gastric cancer [166] . Among hsamiR-335 targeted genes is Fzd-3, a member of the FZD receptor family, upregulated in several cancers [167] . Metastatic potential of gastric cancer cells have been associated with changes in the expression profile of miRNAs involved in regulating Wnt signaling pathway.…”
Section: Role Of Micrornas In Wnt/b-catenin Signaling In the Gastric mentioning
confidence: 99%
“…We observed key oncogenic protein domains (families) frequently found in DMSO but not in treatment, such as histone deacetylase interacting, PI3-kinase, p85-and Ras binding domains and DNA polymerase A/B families. Notably frizzled protein, which activates the Wnt pathway is ranked as the top DMSO-unique proteins [20]. A full list of condition specific domain annotation is shown in Table S1.…”
Section: Treatment Induced Nontrivial Splicing Signals In Lncap Cell mentioning
confidence: 99%